Melt Derivied Fabrication Of Bioactive Glass And Biocompability Evaluation Towards Dental Pulp Stem Cell - Zain, Nurul Shazwani Mohd (2018)
Bioactive glass (BG) has the ability to bond to hard and soft tissues, and promotes bone growth. BG 45S5, with composition of 46.1% SiO2, 26.9% CaO, 24.4% Na2O, and 2.5% P2O5 in mole percentages (mol.%), and a new composition (BG 44S), with similar network connectivity were fabricated via melt derived route using similar melting temperature and soaking time. The 44S composition was proposed to decrease melting temperature during fabrication. The BG preparations included batching, mixing, melting at 1400 °C, water quenching, milling, and sieving. BG 45S5 possessed lower average particle size (11.8 μm) based on the particle size analysis. Both BG were in amorphous phase based on X-Ray Diffraction (XRD) analyses and contained mainly silicate network, with Si-O-Si functional groups, using Fourier Transform Infrared spectroscopy. Both BG were subjected to simulated body fluid incubation to assess the bioactivity for hydroxyl carbonate apatite (HCA) layer formation, followed by characterisations. Functional groups of P-O and C-O bonds, which attributed to HCA layer formation were present at day 1 for BG 44S, and at day 7 for BG 45S5. The hydroxyapatite (HA) layer started to develop on both BG surfaces at day 1, followed by formation of HCA cluster crystal at day 21 based on Scanning Electron Microscope (SEM) images and Energy Dispersive X-ray Spectroscopy (EDX) analyses upon immersion in SBF solution.